1997
DOI: 10.1075/ijcl.2.1.07ray
|View full text |Cite
|
Sign up to set email alerts
|

Social Differentiation in the Use of English Vocabulary

Abstract: In this article, we undertake selective quantitative analyses of the demographi-cally-sampled spoken English component of the British National Corpus (for brevity, referred to here as the ''Conversational Corpus"). This is a subcorpus of c. 4.5 million words, in which speakers and respondents (see I below) are identified by such factors as gender, age, social group, and geographical region. Using a corpus analysis tool developed at Lancaster, we undertake a comparison of the vocabulary of speakers, highlightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 0 publications
14
73
1
Order By: Relevance
“…Rayson et al (1997) found the forms said and says strikingly high up among the most frequently used words in social classes C2 and DE. In the NC, both said and says are overwhelmingly used as quotatives introducing direct speech presentation.…”
Section: Speakermentioning
confidence: 99%
See 2 more Smart Citations
“…Rayson et al (1997) found the forms said and says strikingly high up among the most frequently used words in social classes C2 and DE. In the NC, both said and says are overwhelmingly used as quotatives introducing direct speech presentation.…”
Section: Speakermentioning
confidence: 99%
“…The demographically-sampled subcorpus (henceforth BNC-C) consists of roughly 4.5 million words and is often referred to as the 'conversational' subcorpus because the transcripts assembled in this subcorpus "consist of casual conversations" (Aston & Burnard 1998: 28;Hoffmann et al 2008: 32-39; see also Rayson et al 1997 andBiber et al 1999: 133).…”
Section: Data Source and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Linguists have gone as far as claiming that hypothesis testing of word frequencies is rarely useful to finding associations, and often leads to misleading results [14]. Others have noted that a measure of dispersion is necessary to improve significance testing [21], or that each significant result should be checked using an effect size measure [9] or manual investigation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Keyword profiling [22], exploiting comparative word frequencies, has been used in the past to investigate the differences between spoken and written language [23], British and American English [24], and language change over time. Rayson [25] extended the keywords methodology to extract key grammatical categories and key domain concepts using tagged data in order to make it scalable.…”
Section: Natural Language Analysismentioning
confidence: 99%